Whole-Genome Sequence Analysis of an Extensively Drug-Resistant Salmonella enterica Serovar Agona Isolate from an Australian Silver Gull (Chroicocephalus novaehollandiae) Reveals the Acquisition of Multidrug Resistance Plasmids - Max L. Cummins (American Society for Microbiology, 2020)
ABSTRACT Although most of the approximately 94 million annual human cases of gastroenteritis due to Salmonella enterica resolve without medical intervention, antimicrobial therapy is recommended for patients with severe disease. Wild birds can be natural hosts of Salmonella that pose a threat to human health; however, multiple-drug-resistant serovars of S. enterica have rarely been described. In 2012, silver gull (Chroicocephalus novaehollandiae) chicks at a major breeding colony were shown to host Salmonella, most isolates of which were susceptible to antibiotics. However, multiple-drug-resistant (MDR) Escherichia coli with resistance to carbapenems, ceftazidime, and fluoroquinolones was reported from this breeding colony. In this paper, we describe a novel MDR Salmonella strain subsequently isolated from the same breeding colony. SG17-135, an isolate of S. enterica with phenotypic resistance to 12 individual antibiotics but only nine antibiotic classes including penicillins, cephalosporins, monobactams, macrolides, fluoroquinolones, aminoglycosides, dihydrofolate reductase inhibitors (trimethoprim), sulfonamides, and glycylcyclines was recovered from a gull chick in 2017. Whole-genome sequence (WGS) analysis of SG17-135 identified it as Salmonella enterica serovar Agona (S. Agona) with a chromosome comprising 4,813,284 bp, an IncHI2 ST2 plasmid (pSG17-135-HI2) of 311,615 bp, and an IncX1 plasmid (pSG17-135-X) of 27,511 bp. pSG17-135-HI2 housed a complex resistance region comprising 16 antimicrobial resistance genes including blaCTX-M-55. The acquisition of MDR plasmids by S. enterica described here poses a serious threat to human health. Our study highlights the importance of taking a One Health approach to identify environmental reservoirs of drug-resistant pathogens and MDR plasmids. IMPORTANCE Defining environmental reservoirs hosting mobile genetic elements that shuttle critically important antibiotic resistance genes is key to understanding antimicrobial resistance (AMR) from a One Health perspective. Gulls frequent public amenities, parklands, and sewage and other waste disposal sites and carry drug-resistant Escherichia coli. Here, we report on SG17-135, a strain of Salmonella enterica serovar Agona isolated from the cloaca of a silver gull chick nesting on an island in geographic proximity to the greater metropolitan area of Sydney, Australia. SG17-135 is closely related to pathogenic strains of S. Agona, displays resistance to nine antimicrobial classes, and carries important virulence gene cargo. Most of the antibiotic resistance genes hosted by SG17-135 are clustered on a large IncHI2 plasmid and are flanked by copies of IS26. Wild birds represent an important link in the evolution and transmission of resistance plasmids, and an understanding of their behavior is needed to expose the interplay between clinical and environmental microbial communities.